2022
DOI: 10.1038/s41467-022-35311-4
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal chemotaxis in bacteria

Abstract: Bacteria commonly live in surface-associated communities where steep gradients of antibiotics and other chemical compounds can occur. While many bacterial species move on surfaces, we know surprisingly little about how such antibiotic gradients affect cell motility. Here, we study the behaviour of the opportunistic pathogen Pseudomonas aeruginosa in stable spatial gradients of several antibiotics by tracking thousands of cells in microfluidic devices as they form biofilms. Unexpectedly, these experiments revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
12
1
Order By: Relevance
“…In addition to the chemosensory response, S. aureus PSMs also trigger a “competition sensing” response whereby P. aeruginosa upregulates type VI secretion system and pyoverdine biosynthesis pathways [39]. Similarly, P. aeruginosa has been reported to utilize type IV pili-mediated motility to perform “suicidal chemotaxis” toward antibiotics [58]. The upregulation of these common interbacterial competition pathways supports a model where P. aeruginosa senses potential danger in the environment and responds with directional twitching, while simultaneously activating defense mechanisms to combat the “enemy”.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the chemosensory response, S. aureus PSMs also trigger a “competition sensing” response whereby P. aeruginosa upregulates type VI secretion system and pyoverdine biosynthesis pathways [39]. Similarly, P. aeruginosa has been reported to utilize type IV pili-mediated motility to perform “suicidal chemotaxis” toward antibiotics [58]. The upregulation of these common interbacterial competition pathways supports a model where P. aeruginosa senses potential danger in the environment and responds with directional twitching, while simultaneously activating defense mechanisms to combat the “enemy”.…”
Section: Discussionmentioning
confidence: 99%
“…While PSMs do not affect the P. aeruginosa membrane sufficiently to allow permeabilization, even transient envelope stress may induce T6SS assembly and firing. Interestingly, it has been recently reported that P. aeruginosa chemotaxis towards, instead of away from, antibiotics and releases bacteriocins before dying 54 . While PSMs did not reduce P. aeruginosa viability, we found induction of two pyocins in P. aeruginosa in response to both PSMs pulse-in and co-culture with S. aureus , potentially supporting a similar “suicidal chemotaxis” model.…”
Section: Discussionmentioning
confidence: 99%
“…Four technical replicate images were taken along the length of the capillary, at the top surface of the capillary. The images were then processed through an image analysis pipeline (http://github.com/AroneyS/Capillary-tracking) based on (Oliveira et al, 2022). This pipeline produced individual tracks for each bacterium, calculating the overall swimming speed and the tumble rate.…”
Section: Methodsmentioning
confidence: 99%